2020
DOI: 10.3389/fmicb.2020.585836
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Aquatic and Terrestrial Environments in Chlorella vulgaris (Chlorophyta)

Abstract: Adaptation to Aquatic and Terrestrial Environments in Chlorella vulgaris (Chlorophyta).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…Low-light requirements for growth combined with no signs of photoinhibition even at higher PFDs were also detected in other terrestrial microalgae, for example, in an alpine isolate of Chlorella vulgaris (Aigner et al 2020). Considering the natural light conditions at a tree bark, this terrestrial microhabitat is from an ecophysiological point of view challenging for microalgae, as the bark is exposed to both strong diurnal and seasonal light fluctuations.…”
Section: Light Requirements For Photosynthesis and Growth And Adaptatmentioning
confidence: 87%
See 2 more Smart Citations
“…Low-light requirements for growth combined with no signs of photoinhibition even at higher PFDs were also detected in other terrestrial microalgae, for example, in an alpine isolate of Chlorella vulgaris (Aigner et al 2020). Considering the natural light conditions at a tree bark, this terrestrial microhabitat is from an ecophysiological point of view challenging for microalgae, as the bark is exposed to both strong diurnal and seasonal light fluctuations.…”
Section: Light Requirements For Photosynthesis and Growth And Adaptatmentioning
confidence: 87%
“…Within a relatively short recovery period of 190 min, 85% of the original photosynthetic activity was reached indicating the ability to tolerate desiccation stress for a short time period. This rapid recovery after dehydration is considered characteristic ecophysiological trait of terrestrial microalgae as shown for a terrestrial strain of Chlorella vulgaris (Trebouxiophyceae; Aigner et al 2020), terrestrial strains of Tetradesmus sp. (Chlorophyceae; (Terlova et al 2021) and for the streptophyte Klebsormidium crenulatum (Karsten et al (2010a).…”
Section: Desiccationmentioning
confidence: 95%
See 1 more Smart Citation
“…Vegetative desiccation tolerance is thought to be one of the key traits in the evolution of early land plants as they evolved from aquatic ancestors [5], and considerable research has focused on advancing our understanding of this capacity in mosses, lycophytes, and their immediate algal relatives. This research showed that multiple cellular processes are affected by desiccation including carbon, protein, and lipid metabolism, cell cycle, stress response pathways, and signaling activity (e.g., [4][5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Desert green algae arose multiple times during the diversification of Chlorophyta, often in clades containing both aquatic and terrestrial species [10,13,21,22]. For example, Tetradesmus G.M.…”
Section: Introductionmentioning
confidence: 99%